Resource Revenues and Fiscal Sustainability in Alberta - Shiell, Leslie; Busby, Colin (Université d'Ottawa | University of Ottawa, 2008)
Alberta’s public finances depend upon volatile revenues from an exhaustible resource base. The question arises of what proportion of current resource revenues the government should spend on current priorities and what proportion it should save for future generations. The paper uses the Permanent Resource Income Model to answer the following four questions: -Has Alberta saved enough of its resource revenues to date?-What level of spending out of resource wealth is sustainable moving forward?-What are the implications of a sustainable policy for the province’s current budget planning?-Should Alberta follow Norway’s example of saving all of its resource revenues in a fund and spending only the resulting investment income? / Les finances publiques de l’Alberta dépendent de la volatilité des revenus en provenance de ressources épuisables. La question se pose de savoir quelle proportion des revenus tirés des ressources naturelles le gouvernement devrait dépenser sur les priorités actuelles et quelle proportion devrait être placée pour les générations futures. Cette recherche utilise le Modèle de Revenu Permanent des Ressources afin de répondre aux quatre questions suivantes : -Est-ce que l’Alberta a épargné assez de ses revenus en provenance des ressources?-Quel est le niveau de dépenses soutenable à partir de la richesse des ressources pour aller de l’avant?-Quelles sont les implications d’une politique soutenable pour la planification du budget actuel de la province?-Est-ce que l’Alberta devrait suivre l’exemple de la Norvège de sauver l’ensemble de ses revenues des ressources dans un fonds et de dépenser que les revenus des investissements?
Keywords: Natural resource revenues; Fiscal sustainability; Revenus de ressources e?puisables; soutenabilite? fiscale